Safety and Efficacy of Resident-Performed Gonioscopy-Assisted Transluminal Trabeculotomy. Issue 4 (3rd April 2023) - Patterson, Ian; Avdagic, Ema; Qiu, Mary
Abstract : Précis: GATT can be performed efficaciously and safely by PGY-3 and PGY-4 residents, with clinical outcomes and complication rates that mirror those of attending-performed GATT cohorts from the literature. Purpose: Report outcomes of gonioscopy-assisted transluminal trabeculotomy (GATT) performed by PGY-3 and PGY-4 residents. Methods: A retrospective chart review was performed for patients undergoing resident-performed GATT. Eyes with previous traditional glaucoma surgery (trabeculectomy or aqueous shunt) or neovascular glaucoma were excluded from this analysis. The primary aim was to assess whether resident-performed GATTs demonstrated success rates comparable with the GATT literature. Surgical success was defined as intraocular pressure (IOP)<21 mmHg, and an IOP reduction of 20% from baseline, and no subsequent IOP-lowering surgery. The secondary and tertiary aims were to describe complication rates and operating times for resident-performed GATTs, respectively. Results: A total of 50 eyes from 40 patients with various types of glaucoma were included. Eyes either underwent resident-performed GATT-alone (N=9) or GATT+cataract extraction with intraocular lens implantation (CEIOL) (N=41). The surgical success rate at 6 months was 71% for GATT-alone and 42% for GATT+CEIOL. Three eyes required subsequent IOP-lowering surgery. The hyphema rate was 16% at postoperative week 1 and 6% at postoperative month 1. The IOP spike (>30 mmHg) rate was 18%. Mean surgical time for both GATT-alone and GATT+CEIOL was longer for PGY-4s than for PGY-3s, attributable to less attending assistance during PGY-4 cases and more resident-performed cataracts in PGY-4 GATT+CEIOL cases (85%) compared with PGY-3 cases (35%). Conclusions: GATT can be performed efficaciously and safely by PGY-3 and PGY-4 residents, with clinical outcomes and complication rates that mirror those of attending-performed GATT cohorts from the literature.